2014
DOI: 10.1002/jsfa.6727
|View full text |Cite
|
Sign up to set email alerts
|

Influence of antioxidant compounds, total sugars and genetic background on the chilling injury susceptibility of a non‐melting peach (Prunus persica (L.) Batsch) progeny

Abstract: were selected. The progeny also showed variability for all the evaluated CI symptoms and 16 27 genotypes showed considerable lower susceptibility to CI. After 2 weeks of cold storage, 28 leatheriness and bleeding were the main CI symptoms observed, whereas flesh browning was 29 predominant after 4 weeks. 30 CONCLUSIONS: It was possible to find varieties with high phenolics concentration and 31 relatively low or intermediate CI susceptibility (22, 33, 68, 80, 81, 96 and 120). However, the 32 correlations observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 40 publications
8
34
0
Order By: Relevance
“…Besides being mainly correlated with SSC, consumer acceptance is also dependent on other cultivar attributes such as TA, thus making fruit TA level an eligible target trait for breeders in order to meet consumers requirements. In this study, fruit TA was significantly affected by cultivar ( P = 9.15 × 10 −8 ), fruit type ( P = 8.37 × 10 −3 ), flesh color ( P = 1.82 × 10 −9 ) and fruit shape ( P = 2.92 × 10 −9 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Besides being mainly correlated with SSC, consumer acceptance is also dependent on other cultivar attributes such as TA, thus making fruit TA level an eligible target trait for breeders in order to meet consumers requirements. In this study, fruit TA was significantly affected by cultivar ( P = 9.15 × 10 −8 ), fruit type ( P = 8.37 × 10 −3 ), flesh color ( P = 1.82 × 10 −9 ) and fruit shape ( P = 2.92 × 10 −9 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…persica (Rosaceae) is the second most widely cultivated fruit tree [7]. Peach fruit is known for its nutritional value and therapeutic properties as consequence of its bioactive constituents (phenols and carotenoids) [7][8][9][10][11][12][13]. Thus, in order to evaluate the potential of peach fruits, significance efforts have been directed on the estimation of bioactivity and functionality present in different peach varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Several research papers reported the analysis of bioactive constituents of P. persica using different solvents in the extraction procedure. Among them methanol was the most widely used [7][8][9][10][11][12][13][14] since it offers a high recovery of antioxidant compounds. Differently, the ethanol proves to be least effective solvent for extracting vegetable phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…It is often used to help regulate the function of the digestive system and has been recently used as a supplement for irregularity treatment (7). This effect has been attributed to various compounds present in the fruits, such as dietary fiber, isatin and sorbitol (8). In addition, prunes and prune juice are often used to help regulate the functioning of the digestive system.…”
Section: Introductionmentioning
confidence: 99%